ANALISIS STRATEGI BAURAN PEMASARAN BERDASARKAN SIKLUS HIDUP PRODUK PADA PT. XL AXIATA TBK CABANG MEDAN - agung suripto naibaho (Universitas Sumatera Utara, 2013)
This research aims to determine the presence of XL products in its product life cycle and explain the marketing mix strategy is currently being implemented by PT. XL Axiata Tbk includes product, price, place, promotion, people, and customer service.To measure the stage of XL products in the product life cycle calculated by Polli and Cook method using XL sales revenue from 2007 to 2011. After finding out the position of the XL product life cycle, and then compares and analyzes the marketing mix strategy that is currently implemented by PT. XL Axiata Tbk with alternative strategies should be applied at the stage of product cycle theory at this point according to theories. This study used a qualitative approach which is descriptive comparative. Techniques of data collection in this research conducted based on the knowledge about the XL, an interview with the division related to the purpose of research, journals, websites, and so forth.After doing the calculation according to the method of Polli and Cook, the XL product is currently at the stage of growth in the product life cycle. After doing analyze and comparize according to theories, be concluded that the implemented marketing mix strategy of PT. XL Axiata Tbk appropriate to the position of product in its product life cycle stages at the moment.Keywords: Marketing Mix Strategy, Product Lifecycle.